Peak O2‐pulse predicts exercise training‐induced changes in peak V̇O2 in heart failure with preserved ejection fraction. (15th July 2022) - Mueller, Stephan; Haller, Bernhard; Feuerstein, Anna; Winzer, Ephraim B.; Beckers, Paul; Haykowsky, Mark J.; Gevaert, Andreas B.; Hommel, Jennifer; Azevedo, Luciene F.; Duvinage, André; Esefeld, Katrin; Fegers‐Wustrow, Isabel; et al.
Abstract : Abstract: Aims: Exercise training (ET) has been consistently shown to increase peak oxygen consumption (V̇O2 ) in patients with heart failure with preserved ejection fraction (HFpEF); however, inter‐individual responses vary significantly. Because it is unlikely that ET‐induced improvements in peak V̇O2 are significantly mediated by an increase in peak heart rate (HR), we aimed to investigate whether baseline peak O2 ‐pulse (V̇O2  × HR −1, reflecting the product of stroke volume and arteriovenous oxygen difference), not baseline peak V̇O2, is inversely associated with the change in peak V̇O2 (adjusted by body weight) following ET versus guideline control (CON) in patients with HFpEF. Methods and results: This was a secondary analysis of the OptimEx‐Clin (Optimizing Exercise Training in Prevention and Treatment of Diastolic Heart Failure, NCT02078947) trial, including all 158 patients with complete baseline and 3 month cardiopulmonary exercise testing measurements (106 ET, 52 CON). Change in peak V̇O2 (%) was analysed as a function of baseline peak V̇O2 and its determinants (absolute peak V̇O2, peak O2 ‐pulse, peak HR, weight, haemoglobin) using robust linear regression analyses. Mediating effects on change in peak V̇O2 through changes in peak O2 ‐pulse, peak HR and weight were analysed by a causal mediation analysis with multiple correlated mediators. Change in submaximal exercise tolerance (V̇O2 at the ventilatory threshold, VT1) was analysed as a secondary endpoint. Among 158 patients with HFpEF (66% female; mean age, 70 ± 8 years), changes in peak O2 ‐pulse explained approximately 72% of the difference in changes in peak V̇O2 between ET and CON [10.0% (95% CI, 4.1 to 15.9), P  = 0.001]. There was a significant interaction between the groups for the influence of baseline peak O2 ‐pulse on change in peak V̇O2 (interaction P  = 0.04). In the ET group, every 1 mL/beat higher baseline peak O2 ‐pulse was associated with a decreased mean change in peak V̇O2 of −1.45% (95% CI, −2.30 to −0.60, P  = 0.001) compared with a mean change of −0.08% (95% CI, −1.11 to 0.96, P  = 0.88) following CON. None of the other factors showed significant interactions with study groups for the change in peak V̇O2 ( P  > 0.05). Change in V̇O2 at VT1 was not associated with any of the investigated factors ( P  > 0.05). Conclusions: In patients with HFpEF, the easily measurable peak O2 ‐pulse seems to be a good indicator of the potential for improving peak V̇O2 through exercise training. While changes in submaximal exercise tolerance were independent of baseline peak O2 ‐pulse, patients with high O2 ‐pulse may need to use additional therapies to significantly increase peak V̇O2 .